ABOUT THE NECESSITY OF INTERNATIONAL COOPERATION IN REGULATING POPULATION MIGRATION (World Bulletin of Management and Law, 2023)
The article analyzes the current state of the problems associated with population migration in the modern world community, examines the concept, types of migration and the need for further improvement of international cooperation in regulating migration processes in the world